Efficient two‐layer rural electrification planning and techno‐economic assessment integrating renewable sources. Issue 3 (15th December 2021) - Kamal, Md Mustafa; Ashraf, Imtiaz; Fernandez, Eugene
Abstract: Electricity access is a critical factor for social and economic development. Microgrid becomes cost‐effective means to provide access to electricity for the rural community. Rural electrification demands high investment due to its low energy demand and population. Planning of rural electrification is a technical and financial challenge for policymakers. This paper proposes the grid‐connected electrification of the rural community of Uttarakhand (India). An integrated model formed with the solar photovoltaic system, wind energy, and battery. This research aims to provide the optimal cost‐effective solution for the electrification of the rural community. The suggested model is optimized using Differential Algorithm to determine the optimal system configuration, cost of energy, and net present cost. The effectiveness of the proposed DE algorithm is compared with genetic algorithm and particle swarm optimization. The results confirm that the proposed renewable energy‐based microgrid has a total production cost of 5 185 367.04, with a per‐unit cost of energy is 0.20/kWh. The proposed microgrid is a more suitable option for electrification in rural communities with less dependence on the grid and conventional sources.